The effect of momentary tactile contact between interacting strangers on the recipients' impressions of people and institutions - Levi, Hanna R. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1984., 1984)
The purpose of this study is to investigate the effect of momentary tactile contact, between interacting strangers, Ln a functional/professional situation, on the recipients' affective state and evaluative responses. The research was conducted in the library and the supermarket on the campus of Bosphorous University. The tactile interaction in the present study occurred when data collectors either touched or did not touch a student while leaving the library/supermarket. At that time the respondent was handed a questionnaire containing items to be rated about the institutions she/he had just left. As this touch is not unduly intimate and does not lend itself to being interpreted as a negative message, it was hypnthesized that a momentary touch between interacting strangers would be experienced as a mildly pleasant stimulus, and that it would arouse positive affect. It was also predicted that the positive affect would be generalized to positive evaluations of the associated stimuli, namely, the personnel and the environment. A 2 (touch-no touch) x 2 (sex of data collector) x 2 (sex of subject) Anova was performed on the data, testing the effects of contact, sex of data collector and sex of subject. The library data revealed no significant effects related to touch. The supermarket data, on the other hand, revealed significant effects for the evaluations of the affective state and for the ratings of the personnel. No significant main effect for touch was revealed. However, the effect of touch was observed in a three way interaction (touch x sex of data collector x sex of subject). It was found that, in general, female subjects experienced more positive affect, and their evaluations of the supermarket personnel were more positive than that of male subjects'. Female data collectors tended to produce more positive evaluations of the personnel than male data collectors. The most positive affect was experienced be female subjects interviewed but not touched by female data collectors. Evaluation of the supermarket personnel was most positi when female subjects were interviewed but not contacted by female data collectors. In the contact condition, the most positive affect experienced was one in which female subjects were touched by male data collectors. The evaluation of the supermarket personnel was most positive, in the contact condition, when female subjects were touched by male data- collectors. The most negative evaluations, throughout the study have occurred when male subjects were contacted by male data collectors. This present study on the effect of touch emphasized the importance of the functional perspective, in which a nonverbal behavior is not analysed in isolation, but in accordance with other variables. In this study, the characteris tics of the setting in which the touch stimulus occurred proved to be an important determinant of the meaning attribute~ to touch. The fact that the library data yielded no significanl results, whereas the supermarket data revealed significant three way interactions, showed that the effect of touch varied according to the perceived characteristics of these two institutions. The effect of the touch was accentuated by the difference in nature between the two settings, yielding significant results for the supermarket.
Keywords: Interpersonal communication.; Body language.; Communication -- Psychological aspects.; Touch.